Kontruksi Berita BBC dalam Konflik Palestina-Israel: Analisis Framing Media Robert N. Entman - Muwadhoful Akmal (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
Since October 7, 2023, the escalation of the conflict between Palestine and Israel has now become the main focus of the virtual community, highlighting the brutality of the Israeli genocide against Palestine. On the one hand, many media that discuss the issues of the Palestine-Israel conflict include BBC News, whose news coverage is often controversial, both in terms of how they view the conflict and formulate data to become news arguments. The implications of the media framing have the potential for the virtual community to be carried away by the media's perspective. A critical study is needed using Robert Entman's framing analysis method, which is described narratively descriptively and with qualitative methods. From the results of the research that has been found, there is news about the Palestine-Israel conflict that does not match the facts on the ground. This shows that the BBC media deliberately exaggerates its point of view of support for Israel. The media is not neutral but has a